Sound Scattering from Microbubble Distributions Near the Sea Surface - Carey, WM; Roy, RA (Kluwer Academic Publishers, 1993)
Backscatter from the sea surface is thought to be governed by the roughness of the surface and subsurface bubble distributions. At low frequencies, due to the paucity of large bubbles, scattering results primarily from coherent and/or collective scatter from bubbles entrained by the subsurface vorticity or carried to depth by the Langmuir circulation and thermal convection. It is shown that scattering from compact regions is a function of the volume fraction of air and to first order can be described by a Minnaert formula modified with the volume fraction. Measurement of sound scattering from a submerged cloud of bubbles produces low-frequency peaks with large low-frequency target strength consistent with this theory.